Use of recombinant activated factor VII for acute bleeding episodes in acquired hemophilia: final analysis from the Hemostasis and Thrombosis Research Society Registry acquired hemophilia study. Issue 7 (October 2016) - Ma, Alice D.; Kessler, Craig M.; Al-Mondhiry, Hamid A.B.; Gut, Robert Z.; Cooper, David L.
Abstract : The Hemostasis and Thrombosis Research Society Registry was used to monitor the postapproval use and safety of recombinant activated factor VII (rFVIIa). The objective of this article is to evaluate the data from the Hemostasis and Thrombosis Research Society Registry related to rFVIIa-treated bleeding episodes in patients with acquired hemophilia. For each rFVIIa-treated bleeding episode, the initial dose, total dose, average infused dose, number of doses, and treatment duration were calculated. Efficacy was assessed on a three-point scale. Out of the 166 registered patients with acquired hemophilia, 110 patients were treated for 237 bleeding episodes (139 rFVIIa treated); the majority (70%) were in patients older than 60 years. The most frequently reported bleeding locations were subcutaneous (40%) and mucosal (32%). Subcutaneous bleeding episodes were more commonly reported in women (55% vs. 40% men) and white patients (44 vs. 27% black). Of the 139 rFVIIa-treated bleeding episodes, rFVIIa was used as first-line treatment in 127 bleeding episodes. The median initial dose was 90 μg/kg; the median total dose per episode was 333.5 μg/kg. Physician-rated efficacy of rFVIIa for each bleeding episode was reported as 'bleeding stopped' in 85% of bleeding episodes, 'bleeding slowed' in 11% of bleeding episodes, 'no improvement' in 4% of bleeding episodes, and was not documented in 1 bleeding episode. One thromboembolic event was reported; transient neurologic symptoms were reported in a 31-year-old postpartum patient after 110 doses of rFVIIa. Adequate hemostasis was provided for most rFVIIa-treated bleeding episodes at doses largely conforming to the package insert. No major safety concerns were reported.